A Complete Techno-Economical Assessment for the Conversion of the Kotsiatis Landfill in Cyprus into a Waste to Energy Plant - Savva, Petros G.; Costa, Costas; Charalambides, Alexandros G. (My University, 2011)
Human activities give rise to waste materials, which if not recycled or reused, end up in landfills as "waste". Cyprus is one of the new Member States of the European Union and before 2003, specific legislation concerning the safe management of waste was absent, with most of the waste ending up in landfills. The largest landfill in Cyprus, Kotsiatis, is located 17 km from Nicosia, occupying an area of 2ha. The current study focuses on a complete techno-economical assessment concerning the conversion of Kotsiatis into a modem Waste-to-Energy (WtE) plant, including aspects such as marketing and promotional activities needed, financing options and operational costs. Results have shown that the construction of a Waste-to-Energy plant in the area will improve the quality of life and the current environmental problems, and that it is economically viable without governmental subsidy (with a Net Present Value of €2,655,730 and an Internal Rate of Return of 10.5% in our base scenario). Finally, even though the locals in the close vicinity are against such a plant, this is due to them not being aware of the technology and being misinformed by information through local media.
Keywords: Waste-to-Energy; Kotsiatis Landfill in Cyprus; Techno-economical assessment